Multivision 84. (Wien : Wiener Festwochen, 1984)
Bühlman, Max ; Chicken, Andy ; Danner, Gary ; Dee, Andrea ; Distl, Gottfried ; Fleissner, Richard ; Fugers, Paulus ; Geiger, Markus ; Graf, Inge ; Kaligofsky, Werner ; Kempken, Heike ; Meier, John F. ; Pokornik, Brigitte ; Rainald, S. ; Rumpf, Peter Alois ; Saxer, Peter ; v., Alfred ; Zobernig, Heimo ; ZYX
Multivision 84, Wiener Festwochen, Wien, vom 1. - 17. Juni 1984. Auf der Multivisionsanlage der Wiener Verkehrsbetriebe, U-Bahn-Passage Karlsplatz, Wien
Duits
kunstcatalogus